Educational Tourism and Local Development - Marta-Christina Suciu; Marco Savastano; Gheorghe-Alexandru Stativă; Irina Gorelova (Cactus, 2022)
Educational tourism is a new branch of tourism, which has experienced a significant increase in recent times, due to the important benefits it brings to the local communities. Universities and other educational specialized institutions may highly contribute, support and encourage local development through educational tourism. Students who benefit from studying abroad can be considered as symbolic educational tourists, and their stay is considered to have a high potential to generate benefits. The host university may facilitate the development of better relationships between tourists and local communities in order to contribute to the development of the local economy in a sustainable and resilient way. Education tourism has to be taken into account by all educational institutions due to the different learning opportunities that might be better exploited. This paper focuses on some indicators considered to be relevant for educational tourism.